Culturally Dislocated Clients: Self-Validation and Cultural Conflict Issues and Counselling Implications - Ishiyama, F. Ishu (Canadian Journal of Counselling and Psychotherapy, 2007)
The nature of cultural dislocation is discussed in terms of self-validation issues, cultural conflicts, and cultural attachment. A cultural conflict model is presented, which incorporates two cultural conflict dimensions (i.e., host cultural and home cultural conflicts). Both the counsellor role as client-validator and help-seeking issues are explored, with practical suggestions for increasing helper sensitivity in working with culturally dislocated clients.